Quantifying the Impact and Policy Implications of Transitioning to Zonal and Nodal Pricing in the Electricity Market: A South Korean Case Study - Kyuhyeong Kwag; Hansol Shin; Hyobin Oh; Hyeongseok Yun; Hyojeong Yoon; Wook Kim (Applied Sciences)
Electricity markets are transitioning to zonal and nodal pricing to maximize social welfare, improve price signals, and enhance congestion management. South Korea, traditionally reliant on uniform pricing, is evaluating this transition but lacks a detailed impact analysis. This study assessed the impacts of various zonal and nodal pricing schemes on power systems and provided policy implications for this transition. We (1) modeled the power system at various levels of granularity, obtaining a detailed 4579-node representation; (2) constructed a set of zonal and nodal pricing schemes reflecting changes in market-clearing models and pricing mechanisms; and (3) performed quantitative analyses through simulations for each scheme. Under the current system marginal price (SMP)-based uniform pricing, the schemes with the least market impact are SMP-based zonal pricing with two bidding zones and extended locational marginal pricing. These results can guide the development of an appropriate pricing transition pathway, although a market price reduction of 4.8–7.0% appears inevitable. Within the Korean electricity market, wherein a Transco is a monopoly retailer, we identified potential conflicts of interest for the Transco in zonal and nodal pricing. By focusing on South Korea, this study offers valuable insights into any electricity market considering the transition to zonal and nodal pricing.